Peningkatan Hasil Belajar Siswa Kelas V SD Melalui Model Pembelajaran Project Based Learning (PjBL) - Indah Rahmawati; Indah Primahati; Kiki Rizki Mubarok (Journal of Innovation in Primary Education, 2022)
ABSTRACT This research is a class action research (CAR). This study aims to analyze student learning outcomes in thematic lessons by applying the Project Based Learning (PjBL) learning model in class 5 B SDN Jagasatru 1. PjBL is an innovative learning model that can improve students' ability to collaborate, communicate, solve problems, think critically, creatively, and organize projects that will be carried out by students. This model emphasizes contextual learning through complex activities. Students are required to understand the concept of the core of a material discipline. The PjBL model has great potential in providing a more interesting and meaningful learning experience for students. This model can also help teachers to find out to what extent students are successful in obtaining their learning outcomes. The method used in this research is a quantitative method. Data collection techniques used by using questionnaire techniques and documentation techniques. The results showed that the descriptive analysis of student learning outcomes showed a significant increase. It is known that in cycle 1 many students scored below the KKM with the lowest score of 40 as many as 11 people with a percentage of 37.9% and the highest score of 80 was obtained by 6 people with a percentage of 20.9%. In cycle 2, there was an increase in student learning outcomes. A total of 8 people got a score of 100 with a percentage of 27.6% and the lowest score was 70 which was obtained by 5 people with a percentage of 17.2%. Keywords: PjBL, learning outcomes, students ABSTRAK Penelitian ini merupakan penelitian tindakan kelas (PTK). Penelitian ini bertujuan untuk menganalisis hasil belajar peserta didik pada pelajaran tematik dengan menerapkan model pembelajaran Project Based Learning (PjBL) di kelas 5 B SDN Jagasatru 1. PjBL merupakan salah satu model pembelajaran inovatif yang dapat meningkatkan kemampuan peserta didik untuk berkolaborasi, berkomunikasi, pemecahan masalah, berpikir kritis, kreatif, dan mengorganisasikan proyek yang akan dilakukan oleh peserta didik. Model ini menekankan pada pembelajaran kontekstual melalui kegiatan-kegiatan yang kompleks. Peserta didik dituntut untuk memahami konsep dari inti suatu disiplin materi. Model PjBL memiliki potensi yang besar dalam memberikan pengalaman belajar yang lebih menraik dan bermakna bagi peserta didik. Model ini juga dapat membantu guru untuk mengetahui sampai sejauh mana keberhasil peserta didik dalam perolehan hasil belajarnya. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif. Teknik pengumpulan data yang digunakan dengan menggunakan teknik kuesioner dan teknik dokumentasi. Hasil penelitian menunjukkan bahwa analisis deskriptif terhadap hasil belajar peserta didik menunjukkan kenaikan yang signifikan. Diketahui pada siklus 1 banyak peserta didik memperoleh nilai di bawah KKM dengan nilai terendah 40 sebanyak 11 orang dengan prosentase 37,9 % dan nilai tertinggi sebesar 80 diperoleh sebanyak 6 orang dengan prosentase 20,9 %. Pada siklus 2, terlihat kenaikan terhadap hasil belajar peserta didik. Sebanyak 8 orang memperoleh nilai 100 dengan prosentase 27,6 % dan nilai terendah sebesar 70 yang diperoleh sebanyak 5 orang dengan prosentase 17,2 %. Kata Kunci: PjBL, Hasil belajar, Peserta didik